Determination of Learning Styles among Nursing Students - Pooja Gill; Parul; Yogesh Kumar; Jyoti Sarin (Institute of Medico-legal Publications Pvt Ltd, 2021)
Nursing education furnishes students with the learning qualities required for their profession and also makesstudents lifelong learners. Aim of the study was to evaluate the learning styles among nursing students. Aquantitative approach with descriptive design was applied. A total of 122 students were recruited by purposivesampling from two nursing colleges, selected by convenient sampling. In addition, tools used for the studywere structured questionnaire for sample characteristics and Kolb’s Learning Style Inventory. Learningstyles were assessed after collecting baseline data. Results indicated that the most preferred learning stylewas turned out to be Accommodator (35%). Findings concluded that there is a diversity of learning stylesamong nursing students as the students were having all the types of learning styles.